Current trends in sport climbing injuries after the inclusion into the olympic program. Analysis of 633 injuries within the years 2017/18 - Lutter, Christoph; Tischer, T.; Hotfiel, Thilo; Frank, Luca; Enz, A.; Simon, M.; Schöffl, Volker Rainer (Muscle, Ligaments and Tendons Journal, 2020)
Objective. To prospectively evaluate current demographics, distribution and severity of rock climb-ing-related injuries after the sport’s inclusion into the Olympic program and to analyze changes in comparison to two prior study populations. Methods. In 2017-2018, we performed a single-center injury survey including 436 climbing patients with a total number of 633 independent climbing-related injuries or complaints. Results. 77.1% of the injuries affected the upper extremities, 17.7% the lower and 5.2% other body regions. Injury severity was overall low (Union Internationale des Associations d’Alpinisme (UIAA) metric scale: 1.8 ± 1 (1-4)). The most frequent injuries were finger pulley injuries (12.3%) and finger tenosynovitis (10.6%). 43.9% of reported injuries were acute and 56.1% were chronic. Bouldering accidents were the leading cause of acute injuries (60.4%). Among shoulder injuries, superior labral lesion tears from anterior to posterior (SLAP) represented the leading diagnosis (29.8%). In comparison to our two prior study populations (1998-2001 and 2009-2012), we found: 1) an overall decrease in upper extremity injuries, 2) an increase of lower extremity injuries, 3) a constant decrease of finger pulley injuries and epicondylitis, 4) a rise of knee injuries and shoulder dislocations, 5) an increase of adolescents finger growth plate injuries. Conclusions. Severity of climbing injuries is low overall. Distinct trends are noticeable: being that some injury rates rose while others fell, preventative strategies only seem partially effective. There-fore, adjustment of preventive strategies is required.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Bouldering; Injury surveillance; Lead; Olympia; Speed